Investigating impact of financial stress on FII flows in Indian equity market - Amanjot Singh (Taylor & Francis Group, 2016)
The present study attempts to capture the impact of financial stress prevailing in the Indian as well as US financial system on FII flows in the Indian equity market by employing logistic regression model. The span of monthly data ranges from 2004 to 2014. Owing to non-existence of any standardized index, the study firstly constructs Indian Financial Stress Index. The empirical results have established that with an increase in financial stress in the Indian and US financial system, probability of positive FII flows reduces and consequently the probability of negative flows increases. The results are critically important for the international as well as Indian investors.